Understanding factors influencing the adoption of mHealth by the elderly: An extension of the UTAUT model - Hoque, Rakibul; Sorwar, Golam (International journal of medical informatics (Shannon, Ireland), 2017)
mHealth (mobile health) services are becoming an increasingly important form of information and communication technology (ICT) enabled delivery for healthcare, especially in low-resource environments such as developing countries like Bangladesh. Despite widespread adoption of mobile phones and the acknowledged potential of using them to improve healthcare services, the adoption and acceptance of this technology among the elderly is significantly low. However, little research has been done to draw any systematic study of the elderly’s intention to adopt mHealth services. The aim of this study was to develop a theoretical model based on the Unified Theory of Acceptance and Use of Technology (UTAUT) and then empirically test it for determining the key factors influencing elderly users’ intention to adopt and use the mHealth services. A face-to-face structured questionnaire survey method was used to collect data from nearly 300 participants of age 60 years and above from the capital city of Bangladesh. The data were analyzed using the Partial Least Squares (PLS) method, a statistical analysis technique based upon Structural Equation Modeling (SEM). The study determined that performance expectancy, effort expectancy, social influence, technology anxiety, and resistance to change (p<0.05) had a significant impact on the users’ behavioral intention to adopt mHealth services. The study, however, revealed no significant relation between the facilitating condition and the users’ behavioral intention to use the mHealth services (p>0.05). This study confirms the applicability of UTAUT model in the context of mHealth services among the elderly in developing countries like Bangladesh. It provides valuable information for mHealth service providers and policy makers in understanding the adoption challenges and the issues and also provides practical guidance for the successful implementation of mHealth services. Additionally the empirical findings identify implications related to the design and development of mHealth services that influence potential users. Furthermore, due to a generic approach, the findings of this study could be easily modified to assist other developing countries in the planning and up-take of mHealth services.